Research on the Dissemination Strategy of Traditional Chinese Culture Based on MG Animation - Taking the 24 Solar Terms as an Example - Liu, Angxiao; Liu, Lin (Transactions on Social Science, Education and Humanities Research, 2024)
In the era of globalization, traditional Chinese culture is an important means of telling China’s stories, showcasing cultural soft power, and expanding international influence. This article analyzes the connotation of the 24 solar terms and combines traditional Chinese cultural content with innovative design forms to explore the innovative practice of disseminating the 24 solar terms in dynamic graphic form. It also designs a strategy for disseminating traditional Chinese culture based on MG animation. It provides a certain reference for the inheritance and development of traditional Chinese culture.